2017
DOI: 10.1016/j.expneurol.2017.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Drp1 hyper-activation is protective in animal models of experimental multiple sclerosis

Abstract: Multiple Sclerosis (MS), a leading neurological disorder of young adults, is characterized by the loss of oligodendrocytes (OLs), demyelination, inflammation and neuronal degeneration. Here we show that dynamin-related protein 1 (Drp1), a mitochondrial fission protein, is activated in primary OL cells exposed to TNF-α induced inflammation or oxidative stress, as well as in EAE-immunized and cuprizone toxicity-induced demyelinating mouse models. Inhibition of Drp1 hyper-activation by the selective inhibitor P11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 69 publications
9
53
0
Order By: Relevance
“…2B–E). Consistent with our previous studies [16,18], treatment with P110 had no significant effects on the behavioral status of wildtype mice through the study (Fig. 2).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…2B–E). Consistent with our previous studies [16,18], treatment with P110 had no significant effects on the behavioral status of wildtype mice through the study (Fig. 2).…”
Section: Resultssupporting
confidence: 92%
“…Myelin that is produced by oligodendrocytes wraps the axon and maintains the axonal function. Our previous study demonstrated that inhibition of Drp1 hyperactivation through P110 treatment reduced the loss of the mature oligodendrocytes and repaired demyelination in Multiple Sclerosis (MS) [18]. In zQ175 KI HD mice, we also observed a decrease in myelin basic protein (MBP), which was corrected by P110 treatment.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…[3][4][5] Mitochondria are the main inducer and target of ROS. [3][4][5] Mitochondria are the main inducer and target of ROS.…”
Section: Introductionmentioning
confidence: 99%